KESIAPAN BERWIRAUSAHA YANG DIDUKUNG OLEH KETERAMPILAN BERKOMUNIKASI DAN KETERAMPILAN BERPIKIR KRITIS BAGI SISWA TEKNIK OTOMOTIF - Putra, Rico Andhika; Dianastiti, Yelma (Jurnal Pendidikan Vokasi Otomotif, 2023)
The importance of an entrepreneurial attitude for automotive vocational high school graduates in facing the world of work and creating job opportunities. With a focus on developing communication and critical thinking skills, vocational school students prepare for competitiveness after graduation. Good communication skills help entrepreneurs in starting a business, expanding business networks, and influencing others in a positive way. Conversely, critical thinking skills help in identifying problems, making strategic decisions and facing challenges that may arise in business.This research emphasizes that learning entrepreneurial skills in vocational schools is necessary as an integral part of education. This study uses quantitative methods and focuses on the effect of communication skills and critical thinking on the entrepreneurial readiness of automotive engineering students. The implications of this study support the need for additional skills development apart from skills in students' areas of expertise.An entrepreneur's success depends not only on his or her business idea, but also on the ability to communicate well, think critically, and face challenges with constantly evolving skills. This is a key foundation in entering and surviving in the dynamic and competitive world of entrepreneurship.